Public images, private readings : multi-perspective approaches to the Post-Palaeolithic rock art : proceedings of the XVII UISPP World Congress (1-7 September 2014, Burgos, Spain). - Fábregas Valcarce, Ramón,; Rodríguez-Rellán, Carlos, (Archaeopress Publishing Ltd, 2016)
A significant number of Holocene societies throughout the world have resorted at one time or another to the making of paints or carvings on different places. The aim of the session A11e, held within the XVII World UISPP Congress, was to put together the experiences of specialists from different areas of the Iberian Peninsula and the World.